Risk factors related with avascular necrosis after internal fixation of femoral neck fractures in children: a systematic review and meta-analysis - Qi, Bo-Hai; Wang, Xiao-Wei; Wang, Xiao-Ming; Wang, Huan; Yang, Ya-ting; Jie, Qiang (Frontiers in Pediatrics, 2023)
Background, Less than 1% of children develop femoral neck fractures(FNF), making them uncommon. However, they may have dangerous side effects, like avascular necrosis. Even though several risk factors for postoperative avascular necrosis have been identified, there is still debate regarding them. In this investigation, a meta-analysis was performed to examine the potential causes of postoperative avascular necrosis in children with FNF.Methods We conducted a thorough literature search to find risk factors for avascular necrosis (AVN) after internal fixation of pediatric FNF. Until December 2022, we searched several databases, including PubMed, Embase, Cochrane Library, Web of Science, CNKI, Orthosearch, and Sinomed. Software Zotero 6.0 and Stata 17.0 were used to organise and synthesise the data. Finally, a sensitivity and publication bias test was carried out.Results Our study includes a total of 15 case-control studies involving 814 patients. The risk of postoperative AVN increased with age at fracture encounter (95%ci: 0.64-1.88, P=0.0003)，initial fracture displacement (95% Cl: 1.87-9.54, P=0.0005), and poor fracture reduction (95% Cl:1.95-22.34, P=0.0024) were risk factors for postoperative AVN. There was no significant relationship between gender and postoperative AVN (95% CI: 0.52-1.31, P=0.41). Conversely, Postoperative AVN and reduction methods have no connection with each other. (95% Cl: 0.77-2.66, P=0.25), procedure time (95% Cl: 0.43-2.99, P=0.16), or injury mechanism (95% Cl: 0.32-2.26, P=0.75). The incidence of post-operative AVN varies between Delbet fracture types(95% CI: 0.15-0.31, P < 0.0001), with the overall trend being that the incidence of AVN is highest for type II, lowest for type IV, and close for types I and III. Funnel plots indicate no significant publication bias. Conclusions In this study, About 26% of children who underwent surgery for a femoral neck fracture suffered AVN. The main risk factors for AVN were age, initial displacement of the fractures, and poorly reduced fractures. Gender, timing of the procedure, reduction techniques, or mechanism of injury did not significantly affect the risk. The overall trend in the incidence of AVN for the different Delbet types of fracture is that the incidence of postoperative AVN is highest for type II, lowest for type IV, and close for types I and III.